2020
DOI: 10.1186/s40035-020-00209-y
|View full text |Cite
|
Sign up to set email alerts
|

Does wild-type Cu/Zn-superoxide dismutase have pathogenic roles in amyotrophic lateral sclerosis?

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by adult-onset progressive degeneration of upper and lower motor neurons. Increasing numbers of genes are found to be associated with ALS; among those, the first identified gene, SOD1 coding a Cu/Zn-superoxide dismutase protein (SOD1), has been regarded as the gold standard in the research on a pathomechanism of ALS. Abnormal accumulation of misfolded SOD1 in affected spinal motor neurons has been established as a pathological hallmark of ALS caused by mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 120 publications
1
20
0
Order By: Relevance
“…There is growing evidence that WT SOD1 can be pathogenic in ALS (7,12,13,(87)(88)(89). Interestingly, our WT hSOD1 mus tg mice developed disease.…”
Section: Discussionmentioning
confidence: 66%
“…There is growing evidence that WT SOD1 can be pathogenic in ALS (7,12,13,(87)(88)(89). Interestingly, our WT hSOD1 mus tg mice developed disease.…”
Section: Discussionmentioning
confidence: 66%
“…However, any genetic risk factors or family history in sALS has not been suggested clearly until now, although ALS-related genes (TAR DNA binding protein; TDP-43, Fused in Sarcoma; FUS and Chromosome 9 open reading frame 72; C9orf72) have been linked to sALS 12 16 . Interestingly, inclusion of wild-type (WT)-SOD1 are detected in sALS patients and mouse models with WT-SOD1 overexpression 17 22 . The pathological modification of WT-SOD1 by mutant SOD1 or sALS-related proteins like TDP43 and FUS has been reported 11 , 14 , 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…SOD1 itself is an enzyme whose canonical role is the protective neutralization of reactive oxygen species within cells. While the preponderance of evidence suggests that abnormal, cytotoxic protein aggregation and mitochondrial dysfunction stemming from SOD1 mutations drives pathology in these cases ( Furukawa and Tokuda, 2020 ; Tak et al, 2020 ), it is important to note from a clinical standpoint that KO animal studies have shown SOD1 not to be dispensable ( Sakellariou et al, 2018 ). In fact, loss-of-function mechanisms may play as serious a role as any other factor contributing to ALS pathology, so it is therefore unrealistic to expect that simply eliminating mutant SOD1 will be adequate in human gene therapy for ALS [comprehensively reviewed by Kim et al (2020) ].…”
Section: Introductionmentioning
confidence: 99%